Notes on Chinese Allopachria Zimmermann, with descriptions of two new species from Guangxi (Coleoptera: Dytiscidae) - Bian, Dongju; Ji, Lanzhu (Zootaxa, 2012)
Two new species of the genus Allopachria Zimmermann, 1924: A. elongata sp. nov. and A. yanfengi sp. nov. fromGuangxi Autonomous Region, China are described, illustrated and compared with related species. Allopachria ernsti We-walka, 2002 is recorded from China (Guangxi) for the first time. In addition, a figure of the paramere of Allopachrialiselotteae Wewalka, 2000 is presented and corrected, and the identification of A. dieterlei Wewalka, 2000, recorded from Jiangxi province by Bian & Ji (2010), is changed to A. miaowangi Wewalka, 2010.